2022
DOI: 10.3390/life12050730
|View full text |Cite
|
Sign up to set email alerts
|

Global Crystallographic Texture of Freshwater Bivalve Mollusks of the Unionidae Family from Eastern Europe Studied by Neutron Diffraction

Abstract: The crystallographic texture of the whole valves of bivalve mollusks from the family Unionidae Unio pictorum Linnaeus, 1758 and Anodonta cygnea Linnaeus, 1758 is studied using pole figures measured using neutron diffraction. The use of neutron diffraction, in contrast to X-rays, makes it possible to study the valves without destroying them. Thus, we can discuss the study of the global texture of the entire valve. It was revealed that the pole figures of aragonite in the valves repeat their shape. The pole dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It was previously shown that the crystallographic texture of calcite and aragonite in the shells of bivalve mollusks is very stable over time [30,32], in different parts of the habitat under different climatic conditions [34], and under the influence of trace elements [35]. Some objects showed unusually high sharpness of crystallographic texture [30,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously shown that the crystallographic texture of calcite and aragonite in the shells of bivalve mollusks is very stable over time [30,32], in different parts of the habitat under different climatic conditions [34], and under the influence of trace elements [35]. Some objects showed unusually high sharpness of crystallographic texture [30,33].…”
Section: Introductionmentioning
confidence: 99%
“…The pole figure measurements have been developed for metals and alloys [22,23]. At present, there is a great interest in the crystallographic texture study of biological samples [24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The much greater penetration depth of neutrons in the sample material allows for the investigation of centimeter size samples in transmission geometry, which yields non-destructive texture measurements. Moreover, X-ray or EBSD techniques allow us to study a relatively small part of a valve, while neutron diffraction allows us to measure almost the whole bulk shell [ 16 ]. Complete pole figures can be obtained without intensity corrections by means of neutron diffraction; the grain statistics are better, which is of particular interest for coarse-grained samples [ 17 ].…”
Section: Introductionmentioning
confidence: 99%